2021
DOI: 10.3390/molecules26051349
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Histone Modification by an Electrophilic Derivative of the Anti-HIV Drug Nevirapine

Abstract: Nevirapine (NVP), a non-nucleoside reverse transcriptase inhibitor widely used in combined antiretroviral therapy and to prevent mother-to-child transmission of the human immunodeficiency virus type 1, is associated with several adverse side effects. Using 12-mesyloxy-nevirapine, a model electrophile of the reactive metabolites derived from the NVP Phase I metabolite, 12-hydroxy-NVP, we demonstrate that the nucleophilic core and C-terminal residues of histones are targets for covalent adduct formation. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…With over 37 million people currently being affected worldwide [ 1 , 2 , 3 ] by HIV, the disease remained as one of the major health concerns. While a range of treatments have been introduced to control this disease [ 4 , 5 ] however the high cost often poses an economic burden for patients especially in countries belonging to lower-income group. Launched in the market in 2013 under the umbrella of second generation integrase inhibitors [6] the anti-HIV drug dolutegravir (GSK1349572; brand name ‘Tivicay’) was developed by GlaxoSmithKline (GSK) and Shionogi.…”
Section: Introductionmentioning
confidence: 99%
“…With over 37 million people currently being affected worldwide [ 1 , 2 , 3 ] by HIV, the disease remained as one of the major health concerns. While a range of treatments have been introduced to control this disease [ 4 , 5 ] however the high cost often poses an economic burden for patients especially in countries belonging to lower-income group. Launched in the market in 2013 under the umbrella of second generation integrase inhibitors [6] the anti-HIV drug dolutegravir (GSK1349572; brand name ‘Tivicay’) was developed by GlaxoSmithKline (GSK) and Shionogi.…”
Section: Introductionmentioning
confidence: 99%
“…Histones affect most DNA-related events, including transcription, replication, and chromosome segregation, and play a key role in controlling DNA expression [ 14 , 17 21 ]. Recent evidence has shown that alteration of histones by exogenous toxicants might conceivably disturb their normal function [ 14 , 19 , 22 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleophilic amino residues, such as lysine and cysteine, of proteins are the major modification targets of electrophilic metabolites and intermediates. , Lysine residues play a key role in maintaining normal physiological functions of many proteins. , The primary amine group of lysine in the protein peptide chain is a nucleophilic group that is easily attacked by electrophiles, in particular, those hard electrophiles, to form modified proteins, and these modifications are often associated with chemical-induced toxicity. , Our previous work demonstrated EEA was metabolized to cis -enedial 3 (Scheme ) which sequentially reacted with lysine residues of proteins to form pyrroline derivative 8 (Scheme ), the structure of which was confirmed by NMR . The EEA-derived protein adductions were verified by rationally designed polyclonal antibodies developed in our laboratory …”
Section: Introductionmentioning
confidence: 99%